Highly regioselective, base-catalyzed, biginelli-type reaction of aldehyde, phenylacetone and urea/thiourea kinetic vs. thermodynamic control. (4th March 2018) - Nematpour, Manijeh; Rezaee, Elham; Jahani, Mehdi; Tabatabai, Sayyed Abbas
ABSTRACT: An efficient one-pot regioselective synthesis of various novel 3, 4-dihydropyrimidin-2(1 H )-one (DHPMs) via a three-component Biginelli-type condensation of aldehyde, phenylacetone and urea/thiourea under two different based-catalyzed conditions is described. In kinetic control path, lithium N, N -diisopropylamide (LDA-20 mol % generated in situ from n -BuLi and diisopropylamine) was used as the base, in tetrahydroforane (THF) as the solvent at 0°C. Thermodynamic control path was run with NaH as the base, in EtOH as the solvent under reflux status. The simple procedure, mild base-catalytic reaction conditions, no column chromatography and good to high yields are important features of this protocol. GRAPHICAL ABSTRACT: